Photostimulated changes of properties of CdTe films - Dzhafarov, T. D.; Yesilkaya, S. S. (WILEY-V C H VERLAG GMBH, 2007)
The effect of illumination during the close-spaced sublimation (CSS) growth on composition, structural, electrical, optical and photovoltaic properties of CdTe films and CdTe/CdS solar cells were investigated. Data on comparative study by using X-ray diffraction (XRD), scanning electron microscopy (SEM), absorption spectra and conductivity-temperature measurements of CdTe films prepared by CSS method in dark (CSSD) and under illumination (CSSI) were presented. It is shown that the growth rate and the grain size of CdTe films grown under illumination is higher (by factor about of 1.5 and 3 respectively) than those for films prepared without illumination. The energy band gap of CdTe films fabricated by both technology, determined from absorption spectra, is same (about of 1.50 eV), however conductivity of the CdTe films produced by CSSI is considerably greater (by factor of 10) than that of films prepared by CSSD. The photovoltaic parameters of pCdTe/nCdS solar cells fabricated by photostimulated CSSI technology (J(sc) 28 mA/cm(2), V-oc =0.63 V) are considerably larger than those for cells prepared by CSSD method (J(sc)=22 mA/cm(2), V-oc = 0.52 V). A mechanism of photostimulated changes of properties of CdTe films and improvement of photovoltaic parameters of CdTe/CdS solar cells is suggested.
Keywords: CdTe films; close-spaced sublimation; photostimulated growing; THIN-FILMS; Crystallography